Perancangan Survival Horror Game Out Of Sight Menggunakan Unity 3D Engine - Septian Mahendra Dewantoro; Kartikadyota Kusumaningtyas; Andika Bayu Saputra; Nurul Fatimah (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2022)
A game is the result of the creative expression of a game maker that has an element of entertainment, can be played and has an end goal. In horror games, it is still divided into several more types of games, one of which is a survival horror game that requires players to live against enemy attacks that come their way. This game was created to enrich horror-themed domestically made games. Designing games using the unity 3D engine with the process of applying the MDLC (Media Develpoment Life Cycle) model. A method suitable for game design, starting with the preparation, design, collection of materials, testing and distribution. Out Of Sight game has gameplay with a first-person perspective combined with the survival horror genre. Made with the C# programming language this game is able to run perfectly with various features. There is also a unique feature, namely slowmotion which serves to slow down time to make it easier for players to shoot enemies. This survival horror game has been successfully created and completed. This game conducts testing using black box testing where all features function normally except for the key that serves to open the door. Based on respondents 18.5% said that the door lock had a bug. This game was created to enrich horror-themed domestically made games.